Mobile-Based Application: The Designation of Energy Saving Smart Light System for Monitoring and Controlling - Baharum, Zirawani; Sabudin, Azim Saiful; Yusof, Ernie Mazuin Mohd; Ahmad, Nahdatul Akma (International Journal of Interactive Mobile Technologies (iJIM), 2021)
The use of lights are the command sources in our life, anytime and everywhere. On trending of demands, the alternative sources are important to increase the satisfaction on user requirement. While, saving energy is another issue to be considered on the light system designation. Therefore, this research provides the details on the implementation of the smart lamp with controlled light system based on Arduino and mobile application usage to save the energy. Smart lamp is a finest way to minimize and preserve light with the remote system in order to monitor and control the brightness of light. This research is created to design the energy saving smart light system via mobile application and devices. It is a minor prototype that is fully automated and controlled by Arduino board. The designation begin with identification of input of LDR sensor, PIR sensor and circuit setting. Next, the integration of hardware and software is implemented for Arduino program, mobile application and the devices. Lastly, the testing process is executed and the data is collected and analysed. The overall system has been experimentally validated with the scenario as setup. Through monitoring and controlling the light in such a way is always accurately matched to the actual need that allows to save on the energy usage and costs, as well as to improve the human comfort and efficiency.